Reference governed ADRC approach to manage the handling-comfort contradiction in a full-vehicle suspension. (October 2022) - Muhammed, Alhelou; Yazan, Dayoub; Gavrilov, Alexander
This paper aims to add to the discourse surrounding the development of a new approach to managing the trade-off between the ride-comfort and road-handling experiences induced by car suspension systems. Indeed, at present, management of the handling-comfort contradictions in such a large system using traditional algorithms requires precise modeling and large calculations, for example, model predictive control (MPC) or different models of road disturbances and a genetic representation of the solution domain, such as genetic algorithms. The proposed algorithm takes advantage of the adaptive properties of the active disturbance rejection control (ADRC) to construct a reference governor for the full-car suspension system. Resultant from the proposed algorithm, the required calculations are significantly reduced when compared to the MPC and the performance of the system is constantly monitored. The ADRC focuses on maintaining ride-comfort while the reference governor adjusts the reference signal to maintain the road-handling ability. The results demonstrate how the reference governor optimizes the input reference signals to prevent the suspension deflection from exceeding its imposed limits in instances when required to maintain the greatest degree of road-handling, while simultaneously acting neutrally when the suspension travel is far from the strokes.